PERENCANAAN GEDUNG BEDAH SENTRAL TERPADU (GBST) RUMAH SAKIT BETHESDA YOGYAKARTA - Nisa Utami; Yayan Iswadena (Jurnal Karya Teknik Sipil, 2014)
Integrated Surgical Operation Centre Building of Bethesda Hospital Yogyakarta designed by using Special Moment Resisting Frame System (SMRFS) while the structure was designed earlier in 2011, and re-designed with earthquake load analysis using equivalent static analysis methods. Seismic forces calculated based on area of the earthquake zone 4 as the region has a fairly large earthquake acceleration, so it must be designed earthquake-resistant structures. To realize earthquake resistant structures used Special Moment Resisting Frame System. Frame system is composed of a framework of beams and columns, where the columns are made stronger than the beam (strong column weak beam). To avoid failure of the structure at the beam-column joint, plastic form joint is planned to occur in the beams and columns only occur at the top of the column foundation. Calculation of seismic analysis refers to SNI latest earthquake in 2012. Structure analysis using program SAP2000 v14 to help modeling the structure and determine the forces acting on the structure. Materials used are concrete f'c 30 MPa, where as for steel reinforcement plates and cross bar 240 MPa fy and longitudinal bar fy 400 MPa.